Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1017/s0074180900167130
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in Cool Magnetic CP Stars: Some New Results of Observations, Using CAT (ESO) 2.6m (CrAO), (NOT) La Palma Telescopes

Abstract: Lithium in cool magnetic CP stars in still poorly studied and estimations of the Li abundance in these stars are scarce. There is some evidence of variability of the LiI 6708 Â line, but this variability has not been studied systematicaly. Even the identification of the 6708 Â line with the LiI resonance doublet is still in doubt. This problem is important in the broader context of the Li abundance in various types of stars, as well as for deeper undersfanding of the magnetic star phonomenon itself. The reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…in HD 83368, Sp. A8, Polosukhina et al (1999) found a phase shift between the photometric and magnetic maxima of −0.062 P , and between the central wavelength of the Li 6708Å line and the photometric maximum of +0.029 P . In some cases the light curves in different colors are quite dissimilar, e.g.…”
Section: Introductionmentioning
confidence: 90%
“…in HD 83368, Sp. A8, Polosukhina et al (1999) found a phase shift between the photometric and magnetic maxima of −0.062 P , and between the central wavelength of the Li 6708Å line and the photometric maximum of +0.029 P . In some cases the light curves in different colors are quite dissimilar, e.g.…”
Section: Introductionmentioning
confidence: 90%
“…Model of the oblique rotator explaining the behaviour of the Li i line is shown in Fig. 2 (Polosukhina et al 1999).…”
Section: Main Stages Of the Project Realizationmentioning
confidence: 99%
“…A simple test (Fig. 2) indicates a possible correlation between "Li-deficiency" and Ce abundance, i.e., a star classified by Polosukhina et al (1999) as Li-deficient show no significant overabundance of Ce in its spectrum. Element abundances derived from the whole available spectral region will be used for further, more detailed modelling of the λ 6708 feature in question.…”
Section: Abundance Analysis Of Blend Componentsmentioning
confidence: 99%
“…Moreover, the central wavelength showed a redward shift 0.2Å , varying from star to star. Polosukhina et al (1999) presented the results of the study of the behavior of the Li feature with rotational phase in 8 Ap stars. For four stars in the sample, HD 83368, HD 60435, β CrB and HD 188041, wavelength variations with the rotational period have been discovered and the conclusion has been made that the Li feature can be identified as the resonant Li i doublet and the variability of the feature is explained by the existence of Li rich spots on the stellar surfaces.…”
Section: Introductionmentioning
confidence: 99%